2019
DOI: 10.1038/s41375-019-0478-9
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-phosphate signalling drives an angiogenic transcriptional programme in diffuse large B cell lymphoma

Abstract: Although the over-expression of angiogenic factors is reported in diffuse large B-cell lymphoma (DLBCL), the poor response to anti-VEGF drugs observed in clinical trials suggests that angiogenesis in these tumours might be driven by VEGF-independent pathways. We show that sphingosine kinase-1 (SPHK1), which generates the potent bioactive sphingolipid sphingosine-1-phosphate (S1P), is over-expressed in DLBCL. A meta-analysis of over 2000 cases revealed that genes correlated with SPHK1 mRNA expression in DLBCL w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 69 publications
(92 reference statements)
1
41
0
Order By: Relevance
“…Since peripheral immune cells (especially lymphocytes) do not play a role in organotypic slice culture models, this experimental setup has shown convincingly that siponimod can have beneficial effects in the context of MS by directly modulating the brain cell function. Accordingly, the protective effect of siponimod is not only limited to EAE but has also been observed in other models such as intracerebral hemorrhage [125], where it limits the formation of perihemorrhagic edema, and in experimental stroke [126], where it limits peripheral immune cell recruitment, as well as in a mouse model of diffuse large B-cell lymphoma [127].…”
Section: From Fty720 To Siponimodmentioning
confidence: 90%
“…Since peripheral immune cells (especially lymphocytes) do not play a role in organotypic slice culture models, this experimental setup has shown convincingly that siponimod can have beneficial effects in the context of MS by directly modulating the brain cell function. Accordingly, the protective effect of siponimod is not only limited to EAE but has also been observed in other models such as intracerebral hemorrhage [125], where it limits the formation of perihemorrhagic edema, and in experimental stroke [126], where it limits peripheral immune cell recruitment, as well as in a mouse model of diffuse large B-cell lymphoma [127].…”
Section: From Fty720 To Siponimodmentioning
confidence: 90%
“…Interestingly, tumour angiogenesis meta-signature genes are enriched and correlated with SK1 mRNA expression in a meta-analysis of over 2000 cases of DLBCL (both cell of origin and stromal subtypes). Moreover, S1P induces angiogenic signalling and gene expression programmes that are common to the vasculature of SK1-expressing DLBCL tumours [38]. Therefore, the potential therapeutic benefit of S1P 1 agonists, competitive antagonists and functional antagonists may depend upon the cancer type and further research is warranted.…”
Section: Role Of S1p In Tumour Neovascularisation and Metastasismentioning
confidence: 99%
“…More recently, Lupino et al [ 107 ] demonstrated that the overexpression of SPHK1, one of the two isozymes responsible for the production of sphingosine-1 phosphate (SP1), a bioactive sphingolipid metabolite acting as a potent inducer of angiogenesis [ 108 ], correlates with an angiogenic transcriptional program in DLBCL.…”
Section: Bridging the Gaps Between Disease Biology And Clinical Trmentioning
confidence: 99%